2021
DOI: 10.3390/s21093221
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Attention Levels in ADHD Children with a Video Game and the Measurement of Brain Activity with a Single-Channel BCI Headset

Abstract: Attentional biomarkers in attention deficit hyperactivity disorder are difficult to detect using only behavioural testing. We explored whether attention measured by a low-cost EEG system might be helpful to detect a possible disorder at its earliest stages. The GokEvolution application was designed to train attention and to provide a measure to identify attentional problems in children early on. Attention changes registered with NeuroSky MindWave in combination with the CARAS-R psychological test were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…Table 2 shows the articles that refer to the use of video games as an evaluation tool for the diagnosis of ADHD. Different video games have been designed to evaluate the presence and severity of ADHD nuclear symptoms ( 30 , 72 77 ), prospective memory ( 26 ), executive functions ( 78 ), stress ( 79 ), and prosocial behavior ( 80 ). Serious video games showed high sensitivity and specificity values ( 73 , 75 , 76 ), as well as a high correlation with CPT measurements ( 8 , 72 ) and measurements similar to neuropsychological tests ( 73 ).…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 shows the articles that refer to the use of video games as an evaluation tool for the diagnosis of ADHD. Different video games have been designed to evaluate the presence and severity of ADHD nuclear symptoms ( 30 , 72 77 ), prospective memory ( 26 ), executive functions ( 78 ), stress ( 79 ), and prosocial behavior ( 80 ). Serious video games showed high sensitivity and specificity values ( 73 , 75 , 76 ), as well as a high correlation with CPT measurements ( 8 , 72 ) and measurements similar to neuropsychological tests ( 73 ).…”
Section: Resultsmentioning
confidence: 99%
“…Second, there also exist works that have studied the effect of attention on power bands [ 39 ], and the use of the ratio between —known as the Theta–Beta Ratio (TBR)—has also been reported as an indicator for attention deficit disorder (ADD) or hyperactivity disorder (ADHD) in patients [ 40 ]. Several studies have shown the feasibility of using NM for measuring the attention level [ 41 ]. In [ 42 ], it was shown that there exists a positive correlation between the reported attention level of this device and the self-reported attention levels in an assessment exercise.…”
Section: Methodsmentioning
confidence: 99%
“…For both indexes, the computation algorithms are based on both temporal and frequency domains. According to [ 31 ], the exact algorithm for computation has not been published, but the manufacturer indicates that the Attention index emphasizes beta waves and the Meditation index emphasizes alpha bands. Here, the arousal axis is defined as the difference between Attention and Meditation (Attention – Meditation).…”
Section: Proposed Methodsmentioning
confidence: 99%